ANALISIS PERAN ORGANISASI IMMETA SUMSEL DALAM MENGEMBANGKAN KARAKTER PEDULI SOSIAL DAN PEDULI LINGKUNGAN DI DEPARTEMEN SOSIAL MASYARAKAT DAN LINGKUNGAN - Ansyah, Devi; Kurnisar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role of the Ikatan Mahasiswa Kabupaten Muara Enim Sumatera Selatan (IMMETA Sumsel), particularly the Department of Social Community and Environment, in developing social care and environmental awareness among its members. The background of this study lies in the importance of character education in higher education as an effort to shape a young generation that is responsible, empathetic, and sensitive to social and environmental issues. This research employs a qualitative approach with a case study method, using data collection techniques such as interviews, observations, and documentation involving nine informants, consisting of the general chairperson, three administrators of the Department of Social Community and Environment, and five active members as supporting informants. The findings indicate that the Department of Social Community and Environment of IMMETA Sumsel plays a significant role in fostering both social care and environmental awareness among its members. Through various social and environmental activities, the department not only serves as a platform for developing the potential of student members but also as a medium for cultivating character values, particularly those related to social concern and environmental responsibility.